2008
DOI: 10.1177/0731684408093973
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Treated—Untreated Jute—Carbon and Glass—Carbon Hybrid Composites of Bisphenol-C based Mixed Epoxy—Phenolic Resins

Abstract: Jute-carbon and glass-carbon hybrid composites of mixed matrix material [epoxy resin of bisphenol-C (EBC) and bisphenol-C-formaldehyde (BCF) of 50 wt% of the fibers] have been prepared by hand lay-up technique at 1508C under 7.6 MPa pressure for 2 h. Alkali-treated jute fibers have been acrylated to improve their physico-chemical properties. Tensile strength, flexural strength, electric strength, and volume resistivity of untreated (JCEBCF-50), treated (TJCEBCF-50) jute-carbon and glass-carbon (GCEBCF-50) comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Investigations of the proper fibre treatments for hybrid composites are common in literature [96,157,[160][161][162][163]. These treatments mainly improve the performance of the natural fibre layers on its own, and do not show synergistic effects.…”
Section: Natural Fibre Hybridsmentioning
confidence: 99%
“…Investigations of the proper fibre treatments for hybrid composites are common in literature [96,157,[160][161][162][163]. These treatments mainly improve the performance of the natural fibre layers on its own, and do not show synergistic effects.…”
Section: Natural Fibre Hybridsmentioning
confidence: 99%
“…They found that flexural and impact properties of the composites of alkali-treated jute fabric decreased due to lower mechanical properties of the fibers. It is inferred that jute fabric: vinyl ester resin-based biocomposite made from 5% sodium hydroxide (%w/v) treated jute fabric for 4 hours at 30℃ showed better mechanical properties than other biocomposites [12]. Composite from alkali treated jute–carbon hybrid fabric showed an improvement in tensile and flexural properties of composites 47 and 14%, respectively, in comparison with untreated hybrid fabric [13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the aforementioned processing methods, the resin impregnation method was employed to make oil palm fibre-glass fibre hybrid bilayer laminate epoxy composites 48 and EFB/jute fibre reinforced epoxy hybrid composites 95,96,[101][102][103] Petrucci et al 107 prepared various basalt, glass, flax and hemp fibre epoxy hybrid composite laminates by the vacuum infusion process. The hot press process was used for preparing jute/carbon epoxy and phenolic hybrid composites 69 , sisal/aramid fibre phenolic resin hybrid composites 74 and PALF/glass and sisal/glass fibre reinforced polyester composites 51 . Atiqah et al 45 made kenaf/glass reinforced unsaturated polyester (UPE) hybrid composites for structural applications by SMC.…”
Section: Other Manufacturing Methodsmentioning
confidence: 99%
“…In addition to glass fibres, natural fibres were also hybridised with carbon 69,75,81 and aramid 74 treated hybrid composites were resistant to all chemicals except carbon tetra chloride. Le Guen et al 81 found the damping coefficient of flax/carbon fibre hybrid composites was 4 times higher than that of the carbon fibre composites, but the elastic modulus and strength were lower.…”
Section: Other Hybrid Compositesmentioning
confidence: 99%
See 1 more Smart Citation